IMPLEMENTASI SCRATCH SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN LITERASI DIGITAL GURU SDN RAGUNAN 08 - Millati Izzatillah; Ega Shela Marsiani; Nofita Rismawati (LPPM Universitas Nusa Mandiri, 2026)
The demands of 21st-century education require teachers to possess adequate digital literacy competencies; however, many elementary school teachers remain limited in their ability to utilize technology as interactive learning media. This gap is urgent to address, as failure to integrate technology into teaching practices will hinder the development of critical thinking, creativity, communication, and collaboration skills among students. This community service activity aimed to enhance the digital literacy of 30 teachers at SDN Ragunan 08, comprising both classroom and subject teachers, through the implementation of the Scratch application as an interactive learning medium. Scratch was selected due to its user-friendly interface, visual-based block programming approach, and its capacity to foster creativity in developing interactive learning materials. The implementation method consisted of three stages: socialization, training, and mentoring. The socialization stage raised awareness of the importance of digital literacy in education. The training stage covered basic visual programming, animation creation, and the development of simple interactive learning media using Scratch. The mentoring stage guided teachers in independently designing and developing Scratch-based learning projects applicable in classroom settings. The results demonstrated significant improvement in teachers’ understanding and skills, as evidenced by pre-test and post-test evaluations in which the average score increased from 65 to 85 (a 30.77% improvement). Furthermore, 80% of teachers successfully produced simple interactive learning media, and overall motivation to integrate technology into instructional practices notably increased.